Silver loaded pectin nanoparticles and their anticancer activity - Raheem Hussein, Muayad; Hadi Mohammed, Asmaa; T. M. Noori, Farah (Al-Nahrain Journal of Science, 2024)
A plant-based heteropolysaccharide is recognized for its biocompatibility and biodegradability, making it a promising candidate for green synthesis as a stabilizing agent in the formation of metallic nanostructure. Despite this, Pectin islargely overlooked in the biological industry for MNP production, with no clear reason for its underutilization. A simple and affordable approach for creating Silver Nano products (Ag NPs) have devised by means of citrus pectin forboth a diminishing and stabilizing agent. The Ag NPs have been analyzed through UV-vis, TEM, XRD, and FTIR techniques. The findings reveal that the Ag NPs are spherical, with a consistent, scale of 10 nanometers besides the outstanding dispersion. Moreover, the Ag NPs showed strong anticancer properties. Employing citrus pectin in the synthesis of Ag NPs offers a potential new avenue regarding the effective use of citrus byproducts.